The Peculiar Economics of Professional Sports: A Contribution to the Theory of the Firm in Sporting Competition and in Market Competition - Neale, Walter C. (Quarterly Journal of Economics, 1964)
Louis-Schmelling paradox, 1. — The inverted joint product or the product joint, 2. — League standing effect, 3. — Fourth estate benefit, 3. — Multifirm plants, 5. — Diminishing quality returns, 8. — Input-enthusiasm effect, 8. — Roger Maris cobweb, 12. — Bobby Layne rigidity, 12. — Archie Moore invisibility, 13.